PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAIVARIABEL MODERASI DALAM PERSPEKTIF ISLAM(Studi Pada Perusahaan Sub-Sektor Food and Beverages di Jakarta Islamic Index (JII) 70 Tahun 2018-2022) - kurniawan, Muhammad kurniawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
investment, if the company's financial performance is good, the company's value can be high, on the other hand, if the company's performance is poor, it can be said that the company's value will decrease. Therefore, the company must be able to maintain the survival of the company with a structured and consistent plan in managing all aspects of its business. This is not only beneficial for investors, but also for all stakeholders of a company. This research is a quantitative research with the type of data used is secondary data obtained from the company's official website, the Indonesia Stock Exchange and the Jakarta Islamic Index (JII) 70 for the 2018-2022 period. The population in this study is food and beverages subsector companies listed in the Jakarta Islamic Index (JII) 70 for the 2018-2022 period. The sampling technique in this study uses purposive sampling, the sample in this study consists of 6 companies in the 2018-2022 period so that there are 30 observation data. The data analysis used was Moderated Regression Analysis (MRA) using IBM SPSS Statistic 23 software. The results show that the projected financial performance variables using ROA have a significant positive effect on the projected company value with Tobin's Q. Corporate Social Responsibility cannot moderate the effect of financial performance on company value caused by the low level of corporate social responsibility disclosure.